2012
DOI: 10.1111/j.1365-2427.2012.02796.x
|View full text |Cite
|
Sign up to set email alerts
|

Detrital layers marking flood events in recent sediments of Lago Maggiore (N. Italy) and their comparison with instrumental data

Abstract: Summary 1. A succession of 20 detrital layers was detected in five short cores from the Pallanza Basin in the western part of Lago Maggiore (Italy) by combining thin‐section analyses and high‐resolution micro‐X‐ray fluorescence (μ‐XRF) scanning techniques. The detrital layers range in thickness from 0.6 to 17.4 mm and appear most distinct in the upper 20–25 cm of each core, where eutrophication since the early 1960s resulted in the deposition of a dark, organic sediment matrix. 2. The age‐depth model of previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…They are most discernable in sediment deposited during eutrophic conditions because the intervening sediment with high organic content is extremely dark. Microscopic analyses revealed that the detrital layers typically are graded, with coarse to medium-sized sand grains at the base and silt and clay further up in each layer (Kämpf et al 2011).…”
Section: Hydrodynamic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are most discernable in sediment deposited during eutrophic conditions because the intervening sediment with high organic content is extremely dark. Microscopic analyses revealed that the detrital layers typically are graded, with coarse to medium-sized sand grains at the base and silt and clay further up in each layer (Kämpf et al 2011).…”
Section: Hydrodynamic Variablesmentioning
confidence: 99%
“…These are turbidites (Sturm and Matter 1978) deposited during and after short pulses of detrital matter transport triggered by flood events (Mangili et al 2005). Detrital layers in lake sediment records are valuable proxies for past floods (Kämpf et al 2011), but detailed microfacies and geochemical data are necessary to distinguish between major regional floods and local run-off events or slope failures. Based on the available data, layer thickness is not always a direct measure of flood strength.…”
Section: Cladoceramentioning
confidence: 99%
“…Lago Maggiore is subject to frequent and severe flood events especially in autumn. In the study of Kampf et al. (2012), evidence for the past frequency and magnitude of past flood events is presented based on the presence of visible detrital layers in sediment cores taken from the Pallanza Basin in the north‐western part of the lake.…”
Section: Case Studiesmentioning
confidence: 99%
“…peak discharge or flow velocity) of the event. This is because the thickness of a layer can also be influenced by the distance between the source of the detritus and the studied section and the amount of detritus available at the time of the extreme precipitation and weaker vs. stronger rainfall during the extreme precipitation events (Kämpf et al, 2012(Kämpf et al, , 2015. In addition, over the 9336-year period we investigate, the source of given rainfall events might result in different thickness signatures (Swierczynski et al, 2012(Swierczynski et al, , 2013.…”
Section: Datamentioning
confidence: 99%